Regulating Arbitrary Divorce in Islamic Family Law: A Maqāṣid al-Sharīʿah–Based Comparative Analysis of Muslim-Majority Legal Systems - Fadhilah, Nur; Musonnif, Ahmad; Hadisiswati, Indri (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2025)
This article examines how contemporary Islamic family law regulates arbitrary divorce and evaluates the extent to which such regulation operationalizes maqāṣid al-sharīʿah, particularly as conceptualized by Jamāl al-Dīn ʿAṭiyyah. Arbitrary divorce is understood as unilateral marital dissolution that occurs without adequate judicial oversight, substantive justification, or fair compensation, resulting in harm to women and children. The study asks how different legal systems constrain or reproduce arbitrary divorce and which regulatory model most effectively realizes substantive justice. Employing a qualitative and comparative method, the research analyzes statutory regulations, judicial structures, and doctrinal frameworks governing divorce in Indonesia, Iran, and Algeria as material objects of study. The findings demonstrate three distinct regulatory patterns. Indonesia adopts a procedural model that formally judicializes divorce but fails to prevent substantive injustice due to weak enforcement and partial protection of women’s financial and custodial rights. Iran reflects an administrative–doctrinal model that retains significant male prerogatives while introducing limited compensatory mechanisms. In contrast, Algeria represents a substantive maqāṣid-oriented model in which expanded judicial authority, mandatory reconciliation, and compensation for harm effectively constrain unilateral divorce and promote financial justice and child welfare. The study concludes that effective regulation of arbitrary divorce depends not on procedural formality alone but on the institutional capacity to translate ethical objectives into enforceable outcomes. This maqāṣid-based typology contributes to Islamic family law scholarship by offering a comparative framework for evaluating justice-oriented legal reform.